Surgeons’ non-transparent facemasks challenge the physician–patient relationship in the orthopedic outpatient clinic of a tertiary university hospital during the COVID-19 pandemic: a prospective cohort study of 285 patients - Schneider, Kristian Nikolaus; Theil, Christoph; Gosheger, Georg; Lampe, Lukas Peter; Rödl, Robert; Mellmann, Alexander; Kampmeier, Stefanie; Rickert, Carolin (Acta Orthopaedica, 2022)
Background and purpose — Facemasks play a role in preventing the respiratory spread of SARS-CoV-2, but their impact on the physician–patient relationship in the orthopedic outpatient clinic is unclear. We investigated whether the type of surgeons’ facemask impacts patients’ perception of the physician–patient relationship, influences their understanding of what the surgeon said, or affects their perceived empathy. Patients and methods — All patients with an appointment in the orthopedic outpatient clinic of a tertiary university hospital during the 2-week study period were included. During consultations, all surgeons wore a non-transparent (first study week) or transparent facemask (second study week). Results of 285 of 407 eligible patients were available for analysis. The doctor–patient relationship was evaluated using the standardized Patient Reactions Assessment (PRA) and a 10-point Likert-scale questionnaire ranging from 0 (strongly disagree) to 10 (strongly agree). Results — A non-transparent facemask led to more restrictions in the physician–patient communication and a worse understanding of what the surgeon said. Patients’ understanding improved with a transparent facemask with greatest improvements reported by patients aged 65 years and older (non-transparent: 6 [IQR 5–10] vs. transparent: 10 [IQR 9–10], p < 0.001) and by patients with a self-reported hearing impairment (non-transparent: 7 [IQR 3–7] vs. transparent: 9 [IQR 9–10], p < 0.001). The median PRA score was higher when surgeons wore a transparent facemask (p= 0.003). Interpretation — Surgeons’ non-transparent facemasks pose a new communication barrier that can negatively affect the physician–patient relationship. While emotional factors like affectivity and empathy seem to be less affected overall, the physician–patient communication and patients’ understanding of what the surgeon said seem to be negatively affected.